Identification of factors associated with potential doping behavior in sports: A cross-sectional analysis in high-level competitive swimmers - Devcic, S.; Bednarik, J.; Maric, D.; Versic, S.; Sekulic, D.; Kutlesa, Z.; Bianco, A.; Rodek, J.; Liposek, S. (International Journal of Environmental Research and Public Health, 2018)
Doping behavior, including the misuse of performance-enhancing drugs, is currently a serious problem in sports, and the efficacy of preventive efforts directly depends on information regarding the associations among different precipitating factors (PF) and doping behavior. This study aimed to establish the PF of potential doping behavior (PDB) in competitive swimmers. Methods: The study included 301 swimmers from Slovenia (153 females, 16.4 ± 2.4 years), tested during the 2017 National Championship. Variables were collected by previously validated questionnaires, which included questions on sociodemographics, sports-related factors, consumption of dietary supplements, knowledge of doping, factors of hesitation, and doping-related factors (i.e., number of doping tests, opinion about the presence of doping in sport). The PDB (positive, neutral, or negative intention toward doping) was observed as a criterion, while other variables were included as predictors in multinomial regression analyses (with "negative" as reference value), which additionally controlled for gender and age category (cadet-, junior-, and senior-level) as confounders. Results: The results confirmed higher susceptibility to doping in males (positive: odds ratio (OR): 2.77, 95% confidence interval (CI): 1.27-6.04), those swimmers who reported higher alcohol consumption (neutral: OR: 2.18, 95%CI: 1.06-4.16, positive: OR: 2.14, 95%CI: 1.05-4.37), and those regularly used dietary supplements (positive: OR: 3.62, 95%CI: 1.25-10.52). Competitive achievement in Olympic- (neutral: OR: 0.57, 95%CI: 0.41-0.81, positive: OR: 0.59, 95%CI: 0.39-0.88), and non-Olympic disciplines (positive: OR: 0.54, 95%CI: 0.35-0.83) was protective against PDB. Swimmers who were more concerned about the negative social consequences of doping behavior (i.e., condemnation by family and friends) were less likely to declare a positive intention toward the PDB (family condemnation: OR: 0.69, 95%CI: 0.56-0.86, friends` condemnation: OR: 0.65, 95%CI: 0.52-0.80). Conclusions: The results of the study provide more precise insight into the specific factors associated with PDB in swimming. The established precipitating factors should be incorporated into targeted anti-doping campaigns in this sport.